2018
DOI: 10.1002/jgf2.161
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of fecal colonization with extended‐spectrum β‐lactamase‐producing Enterobacteriaceae in special nursing homes in Japan

Abstract: ObjectiveJapanese welfare facilities for the elderly are called as special nursing home (SNH), providing conventional‐type with group care or unit‐type with individual care. We investigated the risk factors of fecal colonization with extended‐spectrum β‐lactamase‐producing Enterobacteriaceae (ESBL‐E) of elderly who required care at SNH in Japan.MethodsThe feces discharged on diaper were obtained from the total of 100 residents with fecal incontinence in 9 SNHs located in Tokyo, Japan. The samples were cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Overall prevalence of ESBLs-PE carriage in the general population in Netherland from 2013 to 2017 was 4.3% (260/5983) [ 21 ]. Therefore, it is likely the ESBL-PE carriage in the elderly is much higher than that of the general population based on this study and previous reports [ 10 , 11 ]. This might be attributed to more antibiotics exposure in the elderly.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Overall prevalence of ESBLs-PE carriage in the general population in Netherland from 2013 to 2017 was 4.3% (260/5983) [ 21 ]. Therefore, it is likely the ESBL-PE carriage in the elderly is much higher than that of the general population based on this study and previous reports [ 10 , 11 ]. This might be attributed to more antibiotics exposure in the elderly.…”
Section: Discussionsupporting
confidence: 48%
“…The results of this study demonstrate that antimicrobial exposure during the preceding 6 months significantly increased the risk of intestinal ESBL-PE colonization. This is a much longer period than reported in previous studies that showed antibiotic exposure only within the past 3 months or less influenced the intestinal carriage of ESBL-PE [ 10 , 11 , 12 ]. Similarly, the guidelines for hospital-acquired and ventilator-associated pneumonia states that the previous intravenous antibiotic used within the past 3 months was one of the risk factors of multi-drug resistant pathogen infections [ 17 ].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Second, it is possible that nursing staff may have felt more "secure" that isolation was no longer required, and consequently became less compliant with strict adherence to standard precautions. A third possible explanation is that environmental contamination may have played a role [49][50][51], as ESBL-PE can survive on surfaces for many months if disinfection is not well performed [10,52], leading to concerns about direct causality. Consequently, evaluating the environmental contamination and monitoring the established cleaning processes are critical [53].…”
Section: Discussionmentioning
confidence: 99%
“…In other researches, the results reaffirm this relationship, in which patients with intestinal incontinence developed UTI three times more than patients without intestinal incontinence (9,13) . On the other hand, it is important to note that research with urine culture isolates, in addition to reaffirming this association, identified in their findings a high prevalence in NH of elderly people with Enterobacteriaceae producing extendedspectrum beta-lactamase, i.e., multi-resistant bacteria (14)(15) . The authors also emphasize that those with intestinal incontinence should not sit or lie with feces for long periods, as it facilitates the transport of microorganisms, especially when in diarrheal situations.…”
Section: Factors Associated With Urinary Tract Infection In a Nursing Homementioning
confidence: 91%